(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The paper considers the change of an economic system from non renewable to unlimited energy. The Hotelling theorem indicates extracting a non renewable aid in an ideal manner like the source has a tendency to be exhausted when optimally extracted. Nevertheless, it may not be sensible to deplete non-renewable sources of energy that create externalities including Global warming and co2 emissions. The newspaper sets up a canonical development type with damages in the household’s welfare performance as well as 2 sources of energy - renewable and non-renewable energy.